AN INVESTIGATION INTO THE DIFFICULTIES IN COMPREHENSION OF THE TRAGEDY “HAMLET” BY SHAKESPEARE OF THE FOURTH-YEAR STUDENTS IN THE UNIVERSITY OF FOREIGN LANGUAGE STUDIES – THE UNIVERSITY OF DA NANG - Đặng Thị Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This paper attempted to investigate the difficulties in comprehension of the tragedy “Hamlet” by Shakespeare of the fourth-year English major students of the Faculty of Foreign Language Teacher Education at University of Foreign Language Studies – The University of Da Nang (UFLS-UD). The data were collected by means of questionnaires and analyzed both quantitatively and qualitatively. The analysis of data collected from the questionnaires given to 65 students showed that the fourth-year students of Faculty of Foreign Language Teacher Education, UFLS-UD have different attitudes toward learning the play and they are affected by those attitudes. Moreover, the large number of students face a variety of different difficulties when studying English literature in general, “Hamlet” by Shakespeare in particular. The findings were discussed and served as the basis to put forward some proposals to address the problems during the process of reading and analyzing Shakespeare’s classics for learning the tragedy “Hamlet” as well as other masterpieces by Shakespeare. It is hoped that the results of the research might be useful for teachers and learners of English in teaching and learning English literature. Based on the findings, some suggestions were given for handling the obstacles in learning Shakespeare’s classics.